PENGEMBANGAN KENDALI TERBANG BERBASIS SLIDING MODE CONTROL DENGAN ELIMINASI CHATTERING PADA QUADROTOR UNTUK MENGATASI GANGGUAN ANGIN TAK TENTU DI KAWASAN JAWA BARAT - Zuhri, Muhammad Rizki; Wibowo, Singgih Satrio; Soetanto, Maria Fransisca (Jurnal Teknologi Terapan, 2024)
Quadrotors are intrinsically unstable. If there is a sudden wind disturbance, this wind disturbance will be amplified so that the quadrotor's attitude becomes uncontrollable. West Java is one of the regions in Indonesia that has quite high wind disturbances. The recorded daily wind disturbance reached 6.99 m/s with a maximum value of 9.95 m/s. In this research, a control system based on the sliding mode control (SMC) algorithm is used. The advantage of this control algorithm is its ability to compensate for uncertain disturbances. This research investigates the implementation of the SMC control into a quadrotor by incorporating random wind disturbance aspects into the model. The research was carried out numerically with simulations using MATLAB/Simulink, with the position variables being the main focus. Quadrotor equipped with SMC has a lower mean error value for the desired position relative to the real position. This shows that the SMC control algorithm that has been created is able to properly overcome random wind disturbances that occur in the West Java area.